A challenge in diagnosis and treatment in asthma patients with allergic bronchopulmonary aspergillosis: a review - Lukito, Elizabeth Feloni; Chandra, Valencia; Danessa, Gabriela; Wijaya, Meiliyana (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Allergic bronchopulmonary aspergillosis (ABPA) is a common form of fungal-related asthma disease mainly caused by Aspergillus fumigatus. The increasing prevalence of asthma globally and the characteristic of Aspergillus are very easily dispersed in the air to inhale, leading to increased cases of ABPA in asthma patients. Inhalation of conidia Aspergillus spp. can trigger asthma exacerbations due to poor mucociliary clearance. However, the exact pathogenesis is still unclear. Clinical features commonly found in ABPA patients are productive cough with dark green or brown mucus or even hemoptysis. Several criteria for establishing the diagnosis of ABPA can be based on clinical features, laboratory examinations, and imaging, but none has become the gold standard. However, the primary laboratory test utilized for ABPA screening is the measurement of serum-specific IgE levels to A. fumigatus, owing to its high sensitivity. Despite the challenges in finding the most fitting universal consensus, most clinicians still follow the criteria proposed by Rosenberg et al. in 1977. The recommended ABPA treatment is prednisone and/or azole antifungal agents such as itraconazole. In addition, the potential of monoclonal antibodies in ABPA therapy is still under further research. Long-term diagnosis and treatment delays can lead to complications such as bronchiectasis and fibrosis. This review aimed to highlight ABPA in asthma patients, from etiopathogenesis to managing the disease